Internet of Things: Security Issues and Countermeasures - Kamboj, Pradeep; Yadav, Ajit Kumar Singh (International Journal of Computer Sciences and Engineering, 2018)
Internet of Things (IOT) is an emanate trend, that exploits the vast number of inter-connected daily used smartdevices to provide numerous services. These devices may vary in size, computational power, capacity and their usability. Tremendous amount of data is transmitted and collected by these devices, there is a high risk of data theft, object manipulation, identity and network manipulation. Moreover, misuse of IOT devices can also lead to possibility of cyber-attack and to organize crime. While a tremendous rise has been seen in the usage of such devices, security vulnerabilities also rise accordingly. Therefore, it is necessary to identify the security issues and address them accordingly. In this paper we discuss the IoT reference model, some of its applications, security challenges, and their countermeasures. The primary goal of this research is to address security issues in IoT and discuss the countermeasures.